"Oliver Twist" - Lloyd, Frank, 1887-1960; Weil, Harry, 1878-1943; Coogan, Jackie; Chaney, Lon, 1883-1930; Dickens, Charles, 1812-1870.; Sol Lesser Productions; Cinetel Films ([Los Angeles, CA] : Sol Lesser Productions, 1922)
This silent film, directed by Frank Lloyd and adapted from a novel by Charles Dickens, is about an orphan surviving on the streets of London. The main strength of this second screen adaptation of Dickens' classic is in the performances. Although a little young for Oliver (he was not yet 6 years old) this film and The Kid are Jackie Coogan's most important screen appearances. Lon Chaney won praise from the critics for his relatively restrained but effective portrayal of Fagin.
Originally released as a motion picture in 1922.
Jackie Coogan, Lon Chaney, Gladys Brockwell, George Siegmann.
Cinematographers, Glen MacWilliams, Robert Martin; editor, Irene Morra.
This edition silent with English intertitles and musical background, with Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 28, 2015).
Keywords: Twist, Oliver -- (Fictitious character) -- Drama; Orphans -- England -- London -- Drama; London (England) -- History -- 19th century -- Drama; Film adaptations; Silent films; Feature films; Fiction films; Internet videos; Streaming video